Mercury and Mercury-Containing Preparations: History of Use, Clinical Applications, Pharmacology, Toxicology, and Pharmacokinetics in Traditional Chinese Medicine - Zhao, Meiling; Li, Yi; Wang, Zhang (Frontiers in Pharmacology, 2022)
Historically, mercury and mercury-containing preparations have been widely used in traditional Chinese medicine and applied in many clinical practices mainly in the form of mercury sulfides. The clinical application, toxicity manifestations, and symptoms of these preparations largely depend on the route of administration and the dosage form. Commonly used mercury-containing medicinal materials and preparations in traditional Chinese medicine include Cinnabar, an excellent medicine for tranquilizing the nerves; Hongsheng Dan and Baijiang Dan, which have antibacterial, anti-inflammatory, promotion of tissue repair and regeneration and other pharmacological effects. Tibetan medicine commonly uses Zaotai and Qishiwei Zhenzhu pills, which have pharmacological effects such as sedation, anti-inflammatory, anti-convulsant, and improvement of cerebral apoplexy. Menggen Wusu Shibawei pills, commonly used in Mongolian traditional medicine, have the muscle growth and astringent effects. In India and Europe, mercury is often used for treating syphilis. This article summarizes the history, clinical application, pharmacology, toxicology, and pharmacokinetics of mercury and mercury-containing preparations in traditional medicines. In terms of clinical application, it provides suggestions for the rational use and safety of mercury-containing drugs in clinical practices and in public health issues. It will further provide a reference for formulation strategies related to mercury risk assessment and management.